IMPLEMENTASI METODE DISKOVERI PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Halima Halima; Muhammad Taqiyudin; Deri Wanto (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2020)
This study aimed to find out a portrayal of learning implementation using the discovery method by Islamic education teachers in the State Junior High School no. 01 of Ujan Mas, Kepahiang Regency, Bengkulu Province. This study used a qualitative approach, and the informants were teachers, while the subjects observed were Islamic education (PAI) learning activities for grade VII students. In order to garner data in the field, two approaches were used, namely interviews and direct observation. Meanwhile, data analysis adopted the interactive model of Miles and his colleagues by analyzing the data based on four elements of analysis namely data collection, data condensation/data reduction, data display, and drawing conclusion. The conclusion of this study revealed that the implementation of discovery method began by determining learning objectives and determining the method written in the form of a lesson plan (RPP). This method was able to solve students' problems in learning processes and able to lead them to think independently.